In Vitro Laser Fenestration of Aortic Stent‐Grafts: A Qualitative Analysis Under Scanning Electron Microscope. Issue 11 (November 2016) - Lin, Jing; Udgiri, Naval; Guidoin, Robert; Panneton, Jean; Guan, Xiaoning; Guillemette, Maxime; Wang, Lu; Du, Jia; Zhu, Dajie; Nutley, Mark; Zhang, Ze
Abstract: In situ fenestration of stent‐grafts allows patients with life threatening aortic pathologies to be amenable to emergent "off the shelf indications for use" percutaneous treatments as a bail out technique. Three types of aortic stent‐grafts were subjected to laser fenestration in a physiological saline solution followed by balloon angioplasty using 8, 10 or 12 mm in diameter noncompliant balloons. The morphology and the size of fenestrations were observed under optical and scanning electron microscopy. The damage to the fabrics was analyzed and quantified. The creation of fenestrations was feasible in all devices, with varying degrees of fraying and/or tearing. The monofilament twill weave (Medtronic Valiant) tore in two directions (warp and weft) while the multifilament weave fenestrations showed more fraying (Anaconda Vascutek and Zenith TX2 Cook). The size and directions of tearing were more predictable with the 8 mm diameter balloon whereas the results obtained with the 10 and 12 mm diameter balloons were more unpredictable. The fenestrations were free of melting of the yarns and blackening of the filaments. The in situ fenestration is feasible but the observed damage to the fabric constructions must be carefully considered. This procedure must currently be limited to urgent and emergent life threatening cases because it is off indications for use for approved devices.